Specific competences in the Tuning Latin America Project: their degree of importance and achievement among a sample of psychology students - Denise Benatuil; María Juliana Laurito (Universidad de Deusto, 2017)
The implementation of the competence-based education approach at university level is a vehicle for the global transformation of the current Higher Education system. Over the past few decades, psychology has increasingly focused on the identification of core competences in the education of psychologists. The U.S., Canada and Europe have adopted competence-based education approaches. More recently, in 2013 the Tuning Latin America Project introduced the challenge to reach agreement on the education of psychologists in the region. The purpose of this research is to analyse the degree of importance and perceived achievement of the specific competences set out in the Tuning Latin America Project, among a sample of 100 advanced psychology students of a private university in the City of Buenos Aires. For such purpose, the Specific Competences Survey for students of the Tuning Latin America Project was used. All the competences obtained high ratings in terms of importance, in particular those related to professional ethics. In addition, the respondents considered that most of the competences are thoroughly developed during their university training. To conclude, further studies and analyses need to be carried out in order to identify current educational needs for psychologists and thus enhance quality and adjust psychological practice to current social needs.